Adverse Working Conditions and Immigrants' Physical Health and Depression Outcomes. A Longitudinal Study in Greece - Nick Drydakis (Global Labor Organization (GLO), 2021)
Τhe study examines whether adverse working conditions for immigrants in Greece bear an association with deteriorated physical health and increased levels of depression during 2018 and 2019. Findings indicate that workers with no written contract of employment, receiving hourly wages lower than the national hourly minimum wages, and experiencing insults and/or threats in their present job experience worse physical health and increased levels of depression. The study found that the inexistence of workplace contracts, underpayment, and verbal abuse in the workplace may coexist. An increased risk of underpayment and verbal abuse reveals itself when workers do not have a contract of employment and vice versa. Immigrant workers without a job contract might experience a high degree of workplace precariousness and exclusion from health benefits and insurance. Immigrant workers receiving a wage lower than the corresponding minimum potentially do not secure a living income, resulting in unmet needs and low investments in health. Workplace abuse might correspond with vulnerability related to humiliating treatment. These conditions can negatively impact workers' physical health and foster depression. Policies should promote written employment contracts and ensure a mechanism for workers to register violations of fair practices.
Keywords: J81; O15; E24; I14; 330; Adverse Working Conditions; Physical Health; Depression; Immigrants; Refugees; Minimum Wages; Written Contracts of Employment; Threats in job; Workplace precariousness